Does Digitalization Have a Dampening Effect on Income Inequality? Evidence from OIC Countries - Aris Munandar; Misnen Ardiansyah; Dhiyaul Aulia Zulni (Shirkah: Journal of Economics and Business, 2024)
The rapid advancement of digital technology has the capacity to create significant effects on income distribution by shaping the availability and quality of employment opportunities. As a result, it has the potential to either narrow or widen income inequality in society. In this paper, we attempt to test the effect of digitalization on income and wealth inequality. We use a multiproxy of digitalization from the International Telecommunication Union ICT database and comprehensive inequality proxy from the World Inequality Database consisting of 56 Organization of Islamic Cooperation member countries from 2010-2021 and estimate their relationship by performing a fixed-effect panel regression. Our finding reveals that digitalization can alleviate income and wealth inequality. Its narrowing effect also applies to income gender inequality. The decline in income inequality is associated with lower GDP per capita, higher net inflow of foreign direct investment, and greater political stability. Similarly, lower wealth inequality is linked to lower GDP per capita and improved political stability. In light of these results, we recommend that governments implement policies aimed at fostering technological advancements, such as infrastructure development to enhance internet and telecommunication coverage. Additionally, inclusive economic growth policies should be prioritized, along with efforts to attract foreign investment through business-friendly reforms and the promotion of political stability that is devoid of gender discrimination.